1997
DOI: 10.1111/j.1532-5415.1997.tb03193.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and the Changes in Maximal Isometric Strength in Men and Women from the Age of 75 to 80 Years

Abstract: Strength alterations with age differed between muscle groups. Undertaking everyday physical activities such as household work, walking, and gardening, which are also the most common physically demanding activities of older people, may play an important role in maintaining strength at an adequate level for independent living.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
202
3
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(220 citation statements)
references
References 12 publications
11
202
3
4
Order By: Relevance
“…The overall deterioration in test performance among the older age groups in the present study is in line with other studies (Aniansson et al 1983;Rantanen et al 1997), although the study designs and testing procedures were not exactly the same. In some tests (backwards walk, stair climbing and dynamic back extension) the younger subjects even improved their performance.…”
Section: Changes In Health-related Fitnesssupporting
confidence: 92%
See 3 more Smart Citations
“…The overall deterioration in test performance among the older age groups in the present study is in line with other studies (Aniansson et al 1983;Rantanen et al 1997), although the study designs and testing procedures were not exactly the same. In some tests (backwards walk, stair climbing and dynamic back extension) the younger subjects even improved their performance.…”
Section: Changes In Health-related Fitnesssupporting
confidence: 92%
“…However, the present study still included subjects with chronic diseases and physically inactive lifestyles. Corresponding selection bias has been reported in other studies (Aniansson et al 1983;Rantanen et al 1997;Rantanen and Heikkinen 1998;Hughes et al 2001;Paterson et al 2004).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Other studies of change in muscle strength over time have shown declines (Bassey & Harries, 1993;Rantanen et al, 1997), no change (Greig et al, 1993), or even gains (Bassey & Harries, 1993;Rantanen et al, 1997) in strength over 4 ± 25 y. A reduction in type II muscle ®bers has been shown in some studies, but no change was found in others.…”
Section: Epidemiology Of Sarcopeniamentioning
confidence: 97%